MASSA TETES AIR HUJAN DALAM ALQURAN (Analisis Ilmiah QS. Az-Zukhruf Ayat 11) - septinawati, rizky dwi ratna (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This research particularly examines the meaning of "بقدر" in QS. Az-Zukhruf verse 11 by applying the science of climatology to rainwater levels. This study aims to provide new knowledge regarding the meaning of levels in QS. Az-Zukhruf verse 11. The phenomenon of rain falling to the earth is a natural process and we often feel. The phenomenon of rainwater falling to the earth has a level that has been determined by Allah in the Qur'an to be a mercy, but we often encounter natural disasters caused by the presence of rainwater that falls beyond the capacity of water reservoirs on earth. Thus, to reveal the meaning of the level of rainwater, it takes the discipline of Climatology as an analytical approach. Along with this study, the author applies the Science of Climatology to reveal the calculation of levels in QS. Az-Zukhruf verse 11.This research is a literature study (Library Research) using qualitative research methods, by collecting several paperwork from commentators and scientific scientific journals. The primary data used in this study is the Qur'an QS. Az-Zukhruf verse 11 and books on climatology.The results of the research on the mass of raindrops in Al-Qur’an by implementing the discipline of Climatology are to reveal the meaning of rainwater content in QS. Az-Zukhruf verse 11 and the results of the calculation of the mass of raindrops in the Quran.